Assessing the Quality of Concrete Tunnel Lining Exposed to Tunnel Fire through Residual Compressive Strength. (7th April 2023) - Alhawat, Husen; Hamid, R.; Baharom, Shahrizan; Azmi, M. R.; Kaish, A. B. M. A.
Abstract : Compressive strength performance of concrete after exposure to the elevated temperature is important for evaluating and repairing concrete structures. This paper presents an experimental study to determine the residual compressive strength of concrete used in tunnel lining after exposed to tunnel fire. Two types of concrete tunnel lining segments are evaluated in this study. One of it was constructed using a patented fire-resistant concrete (MYC) containing high volume fly ash and nanosilica (HVFANS). Another concrete tunnel lining segment was constructed using concrete containing silica fume normally used in the current construction, coded as SPC concrete. The drilled core results show that, after exposure to tunnel fire temperature up to around 1045°C, the compressive strength of MYC has dropped to 66% of the design strength. In comparison, the SPC concrete showed a decrease in compressive strength to 62% of design strength. The experimental results confirmed that the SPC segments have shown slightly lower residual compressive strength compared to the MYC segments. However, the MYC tunnel segment shows high resistance to the spalling of cover concrete compared to the SPC tunnel segment. Therefore, it can be said that the residual strength alone is not sufficient to compare the damage of concrete exposed to tunnel fire; the spalling damage observation is similarly important as it is one of the important serviceability criteria for designing concrete structures.